2013
DOI: 10.1016/j.cryobiol.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton structure, pattern of mitochondrial activity and ultrastructure of frozen or vitrified sheep embryos

Abstract: Even though sheep embryo cryopreservation is a commonly used procedure the survival and pregnancy outcomes can vary greatly. This study investigated whether cryopreservation was causing subtle changes in ultrastructure, mitochondrial activity or cytoskeletal integrity. Sheep embryos were either slow cooled in 1.5 M EG (n = 22), or vitrified in 20% EG + 20% DMSO with 0.5 M sucrose in Open Pulled Straws (OPS) (n = 24). One hour after warming the cryopreserved embryos differed from control embryos in that they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…ATP usage was evaluated because previous work has reported that the mechanism of action of hypotaurine as a cryoprotectant is to increase mitochondrial activity, presumably improving viability and integrity of the cell [31, 32]. In the present study, the effects of various cryoprotective agents on mitochondrial activity mirrored the results of the proliferation analysis.…”
Section: Resultsmentioning
confidence: 51%
“…ATP usage was evaluated because previous work has reported that the mechanism of action of hypotaurine as a cryoprotectant is to increase mitochondrial activity, presumably improving viability and integrity of the cell [31, 32]. In the present study, the effects of various cryoprotective agents on mitochondrial activity mirrored the results of the proliferation analysis.…”
Section: Resultsmentioning
confidence: 51%
“…However, in cryopreserved IVP sheep embryos, their function is reduced or absent [2]. Cryopreserved embryos also show cytoskeleton disturbance with actin microfilament disorganization [2,19] that can be caused by cryoprotectants [190]. The ultrastructural evaluation of cryopreserved IVP blastocysts confirmed the presence of more severe cellular damage in these embryos compared to those produced in vivo [18], pointing out the need of research to improve IVP sheep embryo quality and cryotolerance.…”
Section: Evaluation Of Cryopreserved Embryosmentioning
confidence: 81%
“…Mitochondria are important for embryo development and metabolism [108,178,190] and thus can be a predictor of the embryo development potential [17,187]. However, in cryopreserved IVP sheep embryos, their function is reduced or absent [2]. Cryopreserved embryos also show cytoskeleton disturbance with actin microfilament disorganization [2,19] that can be caused by cryoprotectants [190].…”
Section: Evaluation Of Cryopreserved Embryosmentioning
confidence: 99%
See 2 more Smart Citations